Crime and Immigration: Evidence from Large Immigrant Waves - Bell, B; Fasani, F; Machin, S (Massachusetts Institute of Technology Press, 2013)
This paper focuses on empirical connections between crime and immigration, studying two large waves of recent U.K. immigration (the late 1990s/early 2000s asylum seekers and the post-2004 inflow from EU accession countries). The first wave led to a modest but significant rise in property crime, while the second wave had a small negative impact. There was no effect on violent crime; arrest rates were not different, and changes in crime cannot be ascribed to crimes against immigrants. The findings are consistent with the notion that differences in labor market opportunities of different migrant groups shape their potential impact on crime. © 2013 by the President and Fellows of Harvard College and the Massachusetts Institute of Technology.